Downregulation of Jun kinase signaling in the amnioserosa is essential for dorsal closure of the Drosophila embryo. - Reed, B.H.; Wilk, R.; Lipshitz, H.D. (Current Biology, 2001)
During Drosophila embryogenesis, Jun kinase (JNK) signaling has been shown to play a key role in regulating the morphogenetic process of dorsal closure, which also serves as a model for epithelial sheet fusion during wound repair. During dorsal closure the JNK signaling cascade in the dorsal-most (leading edge) cells of the epidermis activates the AP-1 transcription factor comprised of DJUN and DFOS that, in turn, upregulates the expression of the dpp gene. DPP is a secreted morphogen that signals lateral epidermal cells to elongate along the dorsoventral axis. The leading edge cells contact the peripheral cells of a monolayer extraembryonic epithelium, the amnioserosa, which lies on the dorsal side of the embryo. Focal complexes are present at the dorsal-most membrane of the leading edge cells, where they contact the amnioserosa.We show that the JNK signaling cascade is initially active in both the amnioserosa and the leading edge of the epidermis. JNK signaling is downregulated in the amnioserosa, but not in the leading edge, prior to dorsal closure. The subcellular localization of DFOS and DJUN is responsive to JNK signaling in the amnioserosa: JNK activation results in nuclear localization of DFOS and DJUN; the downregulation of JNK signaling results in the relocalization of DFOS and DJUN to the cytoplasm. The HINDSIGHT (HNT) Zn-finger protein and the PUCKERED (PUC) JNK phosphatase are essential for downregulation of the JNK cascade in the amnioserosa. Persistent JNK activity in the amnioserosa leads to defective focal complexes in the adjacent leading edge cells and to the failure of dorsal closure.Focal complexes are assembled at the boundary between high and low JNK activity. In the absence of focal complexes, miscommunication between the amnioserosa and the leading edge may lead to a premature "stop" signal that halts dorsalward migration of the leading edge. Spatial and temporal regulation of the JNK signaling cascade may be a general mechanism that controls tissue remodeling during morphogenesis and wound healing.